Genetic divergence in Cork Oak based on cpDNA sequence data - Costa, Joana; Miguel, Célia; Almeida, Helena; Oliveira, Margarida M.; Matos, José a; Simões, Fernanda; Veloso, Manuela; Ricardo, Pinto C.; Paulo, Octávio S.; Batista, Dora (BMC Proceedings, 2011)
The following values have no corresponding Zotero field: periodical: BMC Proceedings issue: Suppl 7
Keywords: Cork oak; cpDNA (voyant); genetic diversity; Populations

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernandez-Llario, P.; Mateos-Quesada, P.; Silvério, A.; Santos, P. (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernández-Llario, P; Mateos-Quesada, P; Silvério, A; Santos, P (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Morphological and physiological response of two populations of Quercus ilex L. to SO2 fumigation - Infante, J M; Garcia-Laureano, R; Merino, J (PHYTON-ANNALES REI BOTANICAE, 2002)
Quercus ilex L., is the predominant evergreen schlerophyllous tree in the Mediterranean landscape of the Iberian Peninsula. Fruit acorns were collected in two populations located in the center (southern Spain) and at the northern border (northern Spain; a distance of 800 km) of the distribution area of Quercus ilex. One-month-old potted plants were grown for 130 days to a high SO2 concentration (0.23 ppm, 14 h d(-1)) under controlled climate conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: air pollution; Mediterranean ecosystems; Populations; Quercus ilex; Sulfur Dioxide